2007
DOI: 10.1590/s0066-782x2007000100009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação ecocardiográfica em obesos graves assintomáticos

Abstract: Objective: To study the systolic and diastolic function of asymptomatic patients with severe obesity using a Doppler echocardiography.Methods: Thirty candidates for bariatric surgery, with an average BMI of 49.2 ± 8.8 Kg/m2 and no previous history of heart disease were evaluated through transthoracic echocardiography. Results:Enlarged left chambers were observed in 42.9% of the sample, diastolic dysfunction in 54.6% and left ventricular hypertrophy in 82.1%, of which 50% of the cases presented the geometric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 26 publications
2
7
0
6
Order By: Relevance
“…When left ventricular diastolic function was assessed, there was a reduction in diastolic function in 53.8% of patients, a fact which is not common in the young age group as in this sample, aged 38.5 years (± 10.5). Okawa's study 24 with 104 morbidly obese patients, found 62.4% of diastolic dysfunction, while another study by Rocha et al 25 found in 30 patients in the preoperative period for bariatric surgery, 54.6% of diastolic dysfunction. Studies on the prevalence of diastolic dysfunction in obese diabetic patients showed a prevalence of 47% when using mitral flow 26 ; Boyer et al 27 , when associated flow propagation and color M-mode tissue Doppler to mitral flow analysis, found a prevalence of 75% of LV diastolic dysfunction, and tissue Doppler detected diastolic dysfunction in 63% of patients.…”
Section: Discussionmentioning
confidence: 92%
“…When left ventricular diastolic function was assessed, there was a reduction in diastolic function in 53.8% of patients, a fact which is not common in the young age group as in this sample, aged 38.5 years (± 10.5). Okawa's study 24 with 104 morbidly obese patients, found 62.4% of diastolic dysfunction, while another study by Rocha et al 25 found in 30 patients in the preoperative period for bariatric surgery, 54.6% of diastolic dysfunction. Studies on the prevalence of diastolic dysfunction in obese diabetic patients showed a prevalence of 47% when using mitral flow 26 ; Boyer et al 27 , when associated flow propagation and color M-mode tissue Doppler to mitral flow analysis, found a prevalence of 75% of LV diastolic dysfunction, and tissue Doppler detected diastolic dysfunction in 63% of patients.…”
Section: Discussionmentioning
confidence: 92%
“…A presença e a intensidade das alterações cardiovasculares em pacientes obesos dependem e são proporcionais ao tempo de instalação e convivência com as alterações hemodinâmicas e gravidade da obesidade (Rocha et al 2007). Portanto, a ausência da elevação significativa da pressão arterial verificada nessa amostra de cães obesos por meio de diferentes métodos de mensuração indireta, pode ser devido ao fato de alguns animais avaliados não apresentarem obesidade pronunciada (escore de condição corporal = 9) ou pelo fato dos cães não possuírem expectativa de vida longa o suficiente em excesso de peso corporal, condição necessária para afetar o controle da pressão arterial sistêmica.…”
Section: Discussionunclassified
“…Bifocal RV pacing has been tested in small studies as a treatment option for patients with LV systolic dysfunction and heart failure. [2][3][4] These studies have shown clinical and echocardiographic improvement 2-4 although in a lesser extent as compared with biventricular pacing. 3 The capacity of shortening the LV activation time with bifocal RV pacing is probably the underlying mechanism to benefit from this pacing mode.…”
Section: Previous Studies On Bifocal Right Ventricular Pacingmentioning
confidence: 99%
“…[2][3][4] These studies have shown clinical and echocardiographic improvement 2-4 although in a lesser extent as compared with biventricular pacing. 3 The capacity of shortening the LV activation time with bifocal RV pacing is probably the underlying mechanism to benefit from this pacing mode. 5,6 However, in accordance with the clinical results, this shortening is higher with biventricular pacing or LV pacing with fusion with intrinsic depolarization.…”
Section: Previous Studies On Bifocal Right Ventricular Pacingmentioning
confidence: 99%